CONTROL OF EDUCATIONAL PROCESSES AND ASSESSMENT OF QUALITY IN HIGHER EDUCATION INSTITUTIONS BASED ON FUZZY SET THEORY - Khamid Azamovich Choriev (Bright Mind Publishing, 2025)
This study examines the approach based on fuzzy set theory for controlling educational processes and assessing the quality of education in higher education institutions. Fuzzy set theory is an effective approach for identifying and evaluating uncertainties in educational processes, playing a key role in overcoming the limitations of traditional assessment systems. This approach helps reduce subjectivity in the educational process, enables more accurate evaluation of students' knowledge and skills, and serves as an effective tool for improving the quality of education.
Keywords: Higher education, education quality, fuzzy set theory, uncertainty management, dynamic assessment system, fuzzy sets, mathematical modeling, knowledge assessment.